Factors Affecting Irritant Contact Dermatitis Among Horticulture Farmers in Semarang District, Indonesia - Yuantari, Maria Goretti Catur; Haikal, Haikal; Susanna, Dewi (Kesmas, 2026)
Irritant contact dermatitis is a common condition among farmers, but its underlying causes remain poorly understood. This study aimed to identify factors associated with irritant contact dermatitis among horticulture farmers in Semarang District, Indonesia. A cross-sectional survey was conducted among 427 farmers using a validated, reliable structured questionnaire. The results indicated complaints of dermatitis related to contact with irritants. Data were analyzed using the Chi-square test and logistic regression. Analysis revealed that sex, personal hygiene habits, education level, and the number of pesticide types used were significantly associated with irritant contact dermatitis. Female farmers were less likely to develop irritant contact dermatitis. Conversely, farmers with poor personal hygiene habits or lower levels of education were more likely to develop the condition. Farmers who used fewer types of pesticides had a lower risk of irritant contact dermatitis than those who used a greater variety. In conclusion, irritant contact dermatitis among farmers is influenced by both work-related exposures and hygiene practices. Improving personal hygiene habits and limiting the use of multiple pesticide types may help prevent irritant contact dermatitis under typical farming conditions.